The Reign of King Douglas Jaja, Jeki IV, Amanyanabo of Opobo Kingdom in the Eastern Niger Delta, 1936-1980 - Edna Adagogo-Brown, Dame (Kashere Journal of Humanities, Management and Social Sciences, 2022)
The crux of this paper is to examine the reign of King Douglas Jaja, Jeki IV, the Amanyanabo of Opobo. During his reign, the state faced succession disputes within the King Jaja Opuwari (the ruling class). King Douglas Jaja 1936-1980 became the fourth ruler under the Jeki Dynasty. During the reign, succession dispute led by Chief Stephen Jaja led to the deposition King Douglas Jaja from being the Head of the Opuwari but continued to reign as the Amanyanabo of Opobo. In order to resolve the issue, the king Jaja house in its entirety resolved to setup a body known as King Jaja Executive Authority. The newly established king Jaja Executive Authority insisted that they had no other person to occupy the throne of King Jaja. This body was able to exercise the executive and legislative functions pending the reinstatement of the Amanyanabo. He was reinstated in 1952 as both the head of the Opuwari and the Amanyanabo of Opobo. This paper seeks to examine the succession dispute in Opobo Kingdom involving King Douglas Jaja between 1936 and 1980. The methodology is qualitative based mainly from secondary sources, particularly from British Records office, London and National Archives, Enugu and Text Books.